The Influence of the Audit Committee on the Value of Banking Sector Companies Listed on the Indonesia Stock Exchange in 2020-2024 - Anbiya Abdul Ghani; Dudi Pratomo (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Firm value reflects a company’s ability to create shareholder wealth and maintain investor confidence, particularly in the banking sector due to its critical role in economic stability. The audit committee as a corporate governance mechanism is expected to enhance firm value; however, previous findings regarding audit committee gender, education, and meeting frequency remain inconsistent. Objective: This study examines the partial and simultaneous effects of audit committee gender, education, and meeting frequency on firm value, with company size as a control variable, among banks listed on the Indonesia Stock Exchange during 2020–2024. Methods: This quantitative study analyzed secondary data from 37 purposively selected banks, comprising 185 bank-year observations. Panel data regression using the Fixed Effect Model was conducted after classical assumption testing and model selection procedures. Results: The findings reveal that audit committee gender, education, and meeting frequency simultaneously affect firm value, but none of these variables has a significant individual effect. Meanwhile, firm size significantly influences firm value, suggesting that investors place greater emphasis on overall corporate fundamentals than individual audit committee characteristics. Conclusion: This study contributes to corporate governance literature by demonstrating that firm value is influenced by the combined effectiveness of governance attributes rather than isolated characteristics. The findings provide practical implications for banking management and regulators in improving audit committee effectiveness and strengthening governance practices.